Strategi Konsolidasi Gapoktan untuk Peningkatan Kapasitas dan Skala Usaha Koperasi Tani BMT Barokah di Kapanewon Jetis, Bantul - Ismiasih; Jamhari; Muh Amat Nasir; Fakhrisha Nur Mahiswari; Disha Mutiara Ramadhanti (Politeknik Piksi Ganesha Indonesia, 2026)
The BMT Barokah Farmers' Cooperative in Kapanewon Jetis, Bantul, Yogyakarta Special Region, has great potential to empower farmers' economies, but faces challenges such as institutional fragmentation, limited business scale, and suboptimal management. This community service program aims to increase the capacity and scale of the cooperative's business through a Gapoktan consolidation approach. The method used is Participatory Rural Appraisal (PRA), which involves outreach, outreach, training, and technology implementation. The results of the activity indicate an increase in partners' understanding of the importance of institutional consolidation, the preparation of business planning documents, and an increase in the capacity of administrators and members in cooperative governance and marketing. In addition, this community service activity has established a strong and independent cooperative institutional model, as well as increased added value for agricultural products through downstream processing .